2020
DOI: 10.1161/circinterventions.119.008671
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin Versus Heparin Monotherapy in Elderly Patients With Myocardial Infarction

Abstract: Background: Elderly patients with acute myocardial infarction undergoing percutaneous coronary intervention are at increased risk of both ischemic and bleeding complications. The optimal anticoagulation strategy in these patients is uncertain. Therefore, we compared bivalirudin to heparin monotherapy in a contemporary cohort of such patients. Methods: A prespecified subgroup analysis of elderly patients with myocardial infarction (≥75 years) from the VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…There was also no substantial benefit from enoxaparin over fondaparinux in decreasing ischemic events. 68 69 However, as with many other trials, no specific outcome in patients ≥ 80 years of age were reported. Moreover, fondaparinux increases catheter thrombosis, primarily excreted by the renal system and contraindicated in advanced renal disease or those undergoing primary percutaneous coronary intervention (PCI).…”
Section: Managementmentioning
confidence: 93%
See 3 more Smart Citations
“…There was also no substantial benefit from enoxaparin over fondaparinux in decreasing ischemic events. 68 69 However, as with many other trials, no specific outcome in patients ≥ 80 years of age were reported. Moreover, fondaparinux increases catheter thrombosis, primarily excreted by the renal system and contraindicated in advanced renal disease or those undergoing primary percutaneous coronary intervention (PCI).…”
Section: Managementmentioning
confidence: 93%
“…There was also no substantial benefit from enoxaparin over fondaparinux in decreasing ischemic events. 68,69 However, as with many other trials, no specific outcome in patients ! 80 years of age were reported.…”
Section: Anticoagulant Therapymentioning
confidence: 95%
See 2 more Smart Citations
“…12 As an indirect inhibitor of thrombin, unfractionated heparin is first synthesized into glycoprotein through the metabolism in the liver, 13 and further combines with antithrombin to form a heparin-antithrombin complex, and then combines with the thrombin catalytic site to exert an action. [14][15][16] During the medication of heparin, if thrombocytopenia occurs in the patient, it will greatly increase the risk of hemorrhage and death. 17 As a synthetic thrombin direct inhibitor, bivalirudin does not require the metabolism in the liver, and can directly bind with thrombin to exert an action.…”
Section: Introductionmentioning
confidence: 99%